The adoption of teaching assistant robots: a technology acceptance model approach. Issue 4 (6th September 2016) - Park, Eunil; Kwon, Sang Jib
Abstract : Purpose: Based on rapid improvements in telecommunications and wireless networks with extensive educational contents, numerous studies have been conducted to improve our educational success/attainment/environment. With this trend, the purpose of this paper is to investigate users' perceptions of teaching assistant (TA) robots and the possible motivations that impact the users' intention to use (IU) the robots. Design/methodology/approach: In light of the rapid development of and attempts at understanding interactions with social robots, including TA robots, this study uses structural equation modeling and confirmatory factor analysis. Findings: The results indicated that perceived usefulness was the most crucial factor determining the users' IU for TA robots. In addition, the relationships of the original technology acceptance model were confirmed. The study findings demonstrated the crucial importance of perceived enjoyment and service quality. Originality/value: Although the role of TA robots has gained user attention, few investigations have been conducted to explain how IU is formed. The current study can thus act as the foundation for exploring the acceptance process in the context of TA robots.